The Intention to Reuse Online Shopping Sites Among Female Shoppers in Saudi Arabia: Applying TAM Model - Alshehri, Manal; Ali, Noor Azman; Sidek, Shafie; Jun-Hwa, Cheah (Advances in Social Sciences Research Journal, 2022)
E-retailers have challenging facing their competitors online according to the huge increase in e-stores and, increase in online shoppers’ awareness toward using online shopping sites. Using the TAM model, this study aimed to measure the effect of perceived ease of use and usefulness, as well as an attitude toward online shopping on women’s intention to reuse online shopping in Saudi Arabia. The quantitative approach was applied in this study with causal and descriptive research. A judgment sampling technique was used in this research, 367 questionnaires have distributed, and only 320 questionnaires were valid to conduct the analysis by using the Structural Equation Model (SEM) in Smart-PLS Software version 3.0. The findings of the study have indicated that perceived ease of use related to usefulness and female shoppers’ attitude toward online shopping positively and have a significant effect on them. On the other hand, perceived usefulness has no significant influence on female shoppers’ attitudes toward online shopping. Finally, female shoppers’ attitude toward online shopping has a positive and significant influence on intention to reuse online shopping sites.